A preliminary study of wildland fire pattern indicator reliability following an experimental fire. (September 2017) - Simeoni, Albert; Owens, Zachary C; Christiansen, Erik W; Kemal, Abid; Gallagher, Michael; Clark, Kenneth L; Skowronski, Nicholas; Mueller, Eric V; Thomas, Jan C; Santamaria, Simon; Hadden, Rory M
An experimental fire was conducted in 2016, in the Pinelands National Reserve of New Jersey, to assess the reliability of the fire pattern indicators used in wildland fire investigation. Objects were planted in the burn area to support the creation of the indicators. Fuel properties and environmental data were recorded. Video and infrared cameras were used to document the general fire behavior. This work represents the first step in the analysis by developing an experimental protocol suitable for field studies and describing how different fire indicators appeared in relation to fire behavior. Most of the micro- and macroscale indicators were assessed. The results show that some indicators are highly dependent on local fire conditions and may contradict the general fire spread. Overall, this study demonstrates that fire pattern indicators are a useful tool for fire investigators but that they must be interpreted through a general analysis of the fire behavior with a good understanding of fire dynamics.